Analisis Pengaruh Motivasi Terhadap Minat Mahasiswa Menjadi Wirausaha - Shilvi Eka Safitri; Ary Dean Amri; Massita Massita; Ananta Apriyani Portuna; Rahayu Julia Ningsih; Windi Juni Lestari (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2024)
This research aims to analyze the influence of motivation on students' interest in becoming young entrepreneurs at Jambi University. Motivation is an important factor that can influence a person's interest in becoming an entrepreneur. This research uses a quantitative approach by collecting data through questionnaires distributed to students at Jambi University. The results of the analysis show that motivation has a significant influence on students' interest in becoming young entrepreneurs at Jambi University. Students who have high motivation tend to have a greater interest in becoming young entrepreneurs. Motivation can come from various factors, such as intrinsic and extrinsic encouragement, the desire to be independent, self-confident, and clear life goals. This research makes an important contribution in understanding the factors that influence students' interest in becoming young entrepreneurs. The results of this research can be used as a reference for universities in increasing student motivation to become young entrepreneurs through relevant and effective approaches. Apart from that, this research can also be a reference for students who are interested in becoming young entrepreneurs to understand the factors that can support success in entrepreneurship.